2007
DOI: 10.7326/0003-4819-146-12-200706190-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Phytoestrogen Genistein on Bone Metabolism in Osteopenic Postmenopausal Women

Abstract: Twenty-four months of treatment with genistein has positive effects on BMD in osteopenic postmenopausal women. ClinicalTrials.gov registration number: NCT00355953.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
203
2
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(230 citation statements)
references
References 44 publications
14
203
2
11
Order By: Relevance
“…In the present study on female rats with normal estrogen levels, both low and high doses of genistein treatment were observed to induce significant increase in BMD, BMC and bone volume, as well as inducing thicker and larger trabecular bone in the mandibular subchondral bone. These results were consistent with the above-mentioned studies on appendicular bone or vertebrae [17,18,20,[30][31][32][33][34][35][36] , indicating that the effect of genistein on mandibular subchondral bone is similar to that on appendicular bone or vertebrae. Similar to the biphasic effects of estrogen depending on dosage [37] , genistein was also observed to have a biphasic cell proliferative response, stimulation at low concentrations and inhibition at high concentrations [38][39][40] .…”
Section: Effect Of Er Silencing On the Effect Of Genistein Treatmentsupporting
confidence: 82%
See 2 more Smart Citations
“…In the present study on female rats with normal estrogen levels, both low and high doses of genistein treatment were observed to induce significant increase in BMD, BMC and bone volume, as well as inducing thicker and larger trabecular bone in the mandibular subchondral bone. These results were consistent with the above-mentioned studies on appendicular bone or vertebrae [17,18,20,[30][31][32][33][34][35][36] , indicating that the effect of genistein on mandibular subchondral bone is similar to that on appendicular bone or vertebrae. Similar to the biphasic effects of estrogen depending on dosage [37] , genistein was also observed to have a biphasic cell proliferative response, stimulation at low concentrations and inhibition at high concentrations [38][39][40] .…”
Section: Effect Of Er Silencing On the Effect Of Genistein Treatmentsupporting
confidence: 82%
“…As shown in Figure 6 and [18,20,[30][31][32][33][34][35][36] . Similarly, oral administration of genistein (54 mg·kg -1 ·d -1 ) increased BMD of the spine and hip in osteopenic postmenopausal Caucasian women with an observation period of 24 months [17] . In the present study on female rats with normal estrogen levels, both low and high doses of genistein treatment were observed to induce significant increase in BMD, BMC and bone volume, as well as inducing thicker and larger trabecular bone in the mandibular subchondral bone.…”
Section: Effect Of Er Silencing On the Effect Of Genistein Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common side effects observed with soy proteins and isoflavones in the present study were abdominal bloating, pain and constipation. Similar side effects have been reported in an earlier study also (36). These harmless yet unpleasant symptoms are usually short-lived and may represent intolerance to proteins.…”
Section: Soy Proteins Vs Isoflavones In Postmenopausal Womensupporting
confidence: 86%
“…Nevertheless, genistein has many other important health benefits, such as lowering the incidence of cardiovascular diseases [12], prevention of osteoporosis, and attenuation of postmenopausal problems [13]. Furthermore, it has been reported that genistein decreases body mass and fat tissue, accompanied by a decreased apetite.…”
Section: Biological Effects Of Genisteinmentioning
confidence: 99%